2008
DOI: 10.3153/jfscom.mug.200726
|View full text |Cite
|
Sign up to set email alerts
|

Otolith Structure, Otolith Dimensions-Fish Length Rela­tionships and Age Determination of Fourspotted Megrim Lepidorhombus boscii (Risso, 1810)

Abstract: Özet:Benekli pisinin kör bölge otolitinde merkez tam ortada bulunurken, gözlü bölge otolitinde ise otolitin posterior kısmına daha yakındır. Bundan dolayı, opak ve hiyalin halkalar kör bölge otolitinde hem anterior hem posterior kısımda gözlenebilirken, gözlü bölge otolitinde merkez posterior tarafa daha yakın olduğu için halkalar bu kısımda çakışmakta ve halka devamlılığının takibi güçleşmektedir. Kör ve gözlü bölge ortalama otolit boyları 4.599 ±0.069 mm ve 4.768 ±0.067 mm (P<0.05), genişlikleri 3.285 ±0.043… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Otolith biometry-body length relationships have been determined for many fish species by different investigators (Gamboa, 1991;Harvey et al, 2000;Waessle et al, 2003;Longenecker, 2008;Battaglia et al, 2010;Zorica et al, 2010;Potier et al, 2011;Skeljo and Ferri, 2012). In Turkey, although a number of studies have been reported on relationships between otolith size and fish length (Şahin and Güneş, 1998;Can, 2000;Ceyhan and Akyol, 2006;Samsun and Samsun, 2006;Bostancı and Polat, 2008;Eroğlu and Şen, 2009;Bostancı et al, 2009;Bostancı et al, 2012;Cengiz et al, 2012;Basusta et al, 2013;Bilge, 2013;İşmen et al, 2013), such information is still lacking for many members of the ichthyofauna. On the other hand, the studies on otolith features of cyprinid fishes have shown an increase in recent years (Şen et al, 2001;Aydin et al, 2004;Bostancı et al, 2007;Gumus et al, 2007;Bostancı, 2009;Bostancı and Polat, 2011;Kontaş, 2012;Basusta et al, 2013;Keskin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Otolith biometry-body length relationships have been determined for many fish species by different investigators (Gamboa, 1991;Harvey et al, 2000;Waessle et al, 2003;Longenecker, 2008;Battaglia et al, 2010;Zorica et al, 2010;Potier et al, 2011;Skeljo and Ferri, 2012). In Turkey, although a number of studies have been reported on relationships between otolith size and fish length (Şahin and Güneş, 1998;Can, 2000;Ceyhan and Akyol, 2006;Samsun and Samsun, 2006;Bostancı and Polat, 2008;Eroğlu and Şen, 2009;Bostancı et al, 2009;Bostancı et al, 2012;Cengiz et al, 2012;Basusta et al, 2013;Bilge, 2013;İşmen et al, 2013), such information is still lacking for many members of the ichthyofauna. On the other hand, the studies on otolith features of cyprinid fishes have shown an increase in recent years (Şen et al, 2001;Aydin et al, 2004;Bostancı et al, 2007;Gumus et al, 2007;Bostancı, 2009;Bostancı and Polat, 2011;Kontaş, 2012;Basusta et al, 2013;Keskin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However some researchers Bostancı and Polat, 2008;Bostancı and Polat, 2009) have determined stronger and positive linear relationships between fish length and otolith size (length, width and weight) in different fish species that have different body form.…”
Section: Resultsmentioning
confidence: 97%
“…In this study, the age class of the four-spotted megrims ranged between 1 and 13 ages. Castilho et al (1993), Vassilopoulou & Ondrias (1999), Robson et al (2000), Bostanci & Polat (2008) and Teixeira et al (2010) reported the longevity limits as 0-12, 0-8, 4-11, 3-8 and 2-9 ages, respectively. Nash & Geffen (2005) stated that the reasons of differences in longevity could be attributed to latitudinal differences as well as to the effects of temperature, intensities of competition for food, food availability, life history strategies and fishing efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Jica (1993) conducted its stock assessment in the Northern Aegean Sea. Bostanci & Polat (2008) studied the otolith structure, otolith dimensions-fish length relationships and age determination of L. boscii. Ismen et al (2007) and Ozekinci et al (2009) reported the length-weight relationships of the four-spotted megrim from Saros Bay.…”
Section: Introductionmentioning
confidence: 99%